AN AGRICULTURAL LAND VALUE ASSESSMENT MODEL - Majstorović, Aleksandar; Dukić, Dragan; Zogović, Mihajlo (Economics of Agriculture, 2013)
The aim of this article is to establish and present a model which is possible and necessary to apply when assessing the value of an agricultural land in the existing economic, legal and market framework of the Republic of Serbia. This article is a preliminary and integral component of a broader research project titled Value Assessment for Various Types of Real Estate in the Republic of Serbia and the Possibility of Their Expression in Accounting, realized at the Faculty of Real Estate Management, Union Nikola Tesla University, Belgrade. The article presents only those preliminary results and the model related to the specified topic, and uses the methods which are successfully employed, in this domain, in the developed countries, primarily in the USA, Germany and France and which are modified with respect to the legal framework and market conditions in the Republic of Serbia. The topic is significant and relevant in light of the announced privatization of 10,000 ha of agricultural land. It is also possible to use this model to re-examine the validity of earlier agricultural land value assessments within the process of privatization of certain agricultural properties.